ACCESSIBILITY AND CHALLENGES TO MENTAL HEALTH SERVICES FOR SCHOOL-GOING CHILDREN IN MALAYSIA FROM STAKEHOLDERS’ PERSPECTIVES - Tengku Mohd, Tengku Amatullah Madeehah; Abang Abdullah, Khadijah Hasanah; Zulkifli, Syara Shazanna; Sanip, Suhaila; Choo, Wan Yuen (Malaysian Journal of Public Health Medicine, 2023)
The prevalence of mental health issues among children and adolescents in Malaysia is a growing concern, amplified by the impact of the COVID-19 pandemic. This paper investigates the avenues through which school-going children and adolescents access public mental health services in Malaysia, the challenges associated with accessing these services and offers recommendations for enhancement. In-depth interviews were conducted with eight stakeholders in the mental health and education sectors, encompassing school counsellors, a family medicine specialist, representatives from the Ministry of Education, and NGO representatives. Thematic analysis was employed to analyse the interview transcripts. Three primary pathways for accessing mental health services were identified: (1) through schools, where counsellors play a key role in initial screening and referrals; (2) via NGOs, which provide support, therapy, and intervention programs; and (3) directly through public health services, including clinics and hospitals. Challenges in accessing these services include trust issues, limited parental awareness, overburdened school counsellors, and stigma. The provision of multiple pathways empowers school children and adolescents to select the most suitable route for seeking help. To address challenges, recommendations include teacher training in basic counselling, regular counsellor training, parental education, awareness campaigns, and the establishment of an efficient referral system with community involvement. Enhancing access to mental health services for school-going children and adolescents in Malaysia necessitates addressing trust issues, raising awareness, and fostering collaboration among stakeholders. Policy reforms and resource allocation are imperative to ensure effective mental health support for this vulnerable population.